2011
DOI: 10.1111/j.1600-0838.2011.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and relaxation intervention for patients with advanced lung cancer: a qualitative feasibility study

Abstract: Lung cancer patients experience loss of physical capacity, dyspnea, pain, reduced energy and psychological distress. The aim of this study was to explore feasibility, health benefits and barriers of exercise in former sedentary patients with advanced stage lung cancer, non-small cell lung cancer (NSCLC) (III-IV) and small cell lung cancer (SCLC) (ED), undergoing chemotherapy. The intervention consisted of a hospital-based, supervised, group exercise and relaxation program comprising resistance-, cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 45 publications
(50 reference statements)
7
100
3
3
Order By: Relevance
“…The patients' reasons for this low adherence rate have been the subject in a recently publish qualitative analysis [36]. Although the patients claimed that the home-based training program was easy to understand, there were substantial reasons why they did not manage to do it.…”
Section: Tablementioning
confidence: 98%
“…The patients' reasons for this low adherence rate have been the subject in a recently publish qualitative analysis [36]. Although the patients claimed that the home-based training program was easy to understand, there were substantial reasons why they did not manage to do it.…”
Section: Tablementioning
confidence: 98%
“…This is supported by a qualitative interview survey of the patient population in this study. 18 Another possible explanation for this increase may be the effect of the relaxation exercises, which in addition to the effect on the overall HRQoL have also been shown to have an effect on emotional well-being. This effect is emphasized in a systematic review of randomized controlled trials of psychological and/or lifestyle interventions for adults with COPD that concluded that complex psychological and/or lifestyle interventions that include an exercise component significantly reduce symptoms of depression and anxiety.…”
Section: 37mentioning
confidence: 99%
“…The nature of symptoms calls for complex interventions designed to address these symptoms, which is why our group designed a multimodal supervised group intervention combined with a home-based walking program that was tested in a feasibility study. 6,18,19 Due to low adherence in the home-based intervention and lack of energy and motivation toward the home-based component, 18 this part was removed in this phase II study. This observation was in line with our previous research, stating that Danish cancer patients have preferences for exercise organized in groups with peers.…”
mentioning
confidence: 99%
“…Study revealed maintaining contact with family and friends for support was important for their quality of life (John, 2010;Eustache et al, 2014). Several strategies such as changing expectations, maintaining positivity, avoiding illness-related thoughts, religion, budgeting time and energy, exercise, relaxation are helpful for cancer patients (John, 2010;Adamsen et al, 2012;Mosher et al, 2015).…”
Section: 6633 Lived Experience Among Patients Newly Diagnosed With Lmentioning
confidence: 99%